Performance of flexible pavements enhanced using geogrid-reinforced asphalt overlays - Correia, Natália de Souza (2014)
The study of innovative pavements is of significant importance in geotechnical engineering in Brazil, due to the continued need to increase the network of roadways. This requires optimized projects, not only for economic, but also for technical reasons. Technical solutions that use geosynthetics in asphalt overlays have been identified to minimize fatigue and reflective cracks. However, the majority of the application of this technology has ignored the possible additional structural benefits brought by the inclusion of geosynthetics as reinforcement in asphalt layers. The objective of this research is to assess the reinforcement benefits of geogrids placed within asphalt overlays on the structural performance of flexible pavements. In addition, this study investigates the tensile-strain response of geogrids under traffic conditions, induced by cyclic wheel loads generated by a new accelerated pavement testing facility (APT) that was specifically developed for this research. The APT facility consists of a large steel testing box, in which field-scale pavement layers could be constructed. Pavement materials included subgrade soil, aggregate base, hot mix asphalt concrete, asphalt emulsion and a PVA geogrid. Pavement performance was assessed by applying a cyclic wheel load pressure of 700 kPa to the pavement surface. The pavement sections investigated in this study included a geogrid-reinforced and an unreinforced asphalt overlay sections, a single new geogrid-reinforced asphalt layer, and a geogrid-reinforced asphalt overlay with reduced base course thickness. A variety of sensors were used to measure asphalt concrete strains, surface plastic and elastic displacements, and induced traffic loads. Displacements along the geogrid specimens were measured using a tell-tail system. As result, several reinforcement mechanisms of this technique could be quantified in the present study. Polymeric geogrid reinforcements were found to have considerably reduced strains developed at the bottom of asphalt layers, as well as to have reduced vertical stresses in pavement lower layers. Resistance to rutting and lateral movement induced by the geogrids were also clearly evidenced in the presented study. The measurement of displacements along the geogrid provided understanding of the distribution of strains during traffic loading. A mobilized length was identified in geogrid-reinforced sections, showing that the bonding between geogrids and asphalt layers and the stiffness of the geogrid ensured satisfactory performance of the pavement sections. The results also illustrated that the lateral restraining mechanisms effect is a governing mechanism to improve the performance of the asphalt layers by the development of shearing resistance with the geogrids. Overall, it was concluded that geogrids within asphalt overlays act as reinforcement and not merely to delay cracks, providing enhanced performance to flexible pavement structures.